Effects of Renal Impairment on the Pharmacokinetics of Abrocitinib and Its Metabolites. (15th February 2022) - Wang, Ellen Q.; Le, Vu; Winton, Jennifer A.; Tripathy, Sakambari; Raje, Sangeeta; Wang, Lisy; Dowty, Martin E.; Malhotra, Bimal K.
Abstract: Abrocitinib, an oral once‐daily Janus kinase 1 selective inhibitor, is under development for the treatment of atopic dermatitis. This phase 1, nonrandomized, open‐label, single‐dose study (NCT03660241) investigated the effect of renal impairment on the pharmacokinetics, safety, and tolerability of abrocitinib and its metabolites following a 200‐mg oral dose. Twenty‐three subjects with varying degrees of renal function (normal, moderate, and severe impairment) were enrolled. Active moiety exposures were calculated as the sum of unbound exposures for abrocitinib and its active metabolites. For abrocitinib, the adjusted geometric mean ratios (GMRs; %) for area under the concentration‐time curve from time 0 extrapolated to infinite time and maximum plasma concentration were 182.91 (90% confidence interval [CI], 117.09‐285.71) and 138.49 (90% CI, 93.74‐204.61), respectively, for subjects with moderate renal impairment vs normal renal function; corresponding GMRs were 121.32 (90% CI, 68.32‐215.41) and 99.11 (90% CI, 57.30‐171.43) for subjects with severe impairment vs normal renal function. Metabolite exposures generally increased in subjects with renal impairment. The GMRs of unbound area under the concentration‐time curve from time 0 extrapolated to infinite time and maximum plasma concentration of active moiety were 210.20 (90% CI, 154.60‐285.80) and 133.87 (90% CI, 102.45‐174.92), respectively, for subjects with moderate renal impairment vs normal renal function. Corresponding values were 290.68 (90% CI, 217.39‐388.69) and 129.49 (90% CI, 92.86‐180.57) for subjects with severe renal impairment vs normal renal function. Abrocitinib was generally safe and well tolerated. Both moderate and severe renal impairment led to higher exposure to abrocitinib active moiety, suggesting that abrocitinib dose should be reduced by half for patients with moderate or severe renal impairment. ClinicalTrials.gov identifier: NCT03660241